Factors which influence the timing of maximum growth rate of the head in low birthweight infants. - Fujimura, M (1977)
The postnatal rate of head growth in 63 infants of less than 34 weeks' gestation was examined retrospectively, together with that of 7 other infants of between 34 and 40 weeks' gestation who had severe respiratory illnesses. From the serial measurements of head circumference the timing of maximum velocity of postnatal head growth was examined and related to the infant's gestational age, nutrition, and respiratory illness during the neonatal period. Within this group of infants the longer the gestation the earlier maximum head growth velocity occurred. For infants of similar gestational ages the presence of a severe respiratory problem was associated with a delay in the time of maximum head growth. Differences in caloric intake during the first week of life did not seem to affect significantly the timing of maximum head growth velocity.